Large Print Nursery Rhymes (India : Om Kidz, 2020)
"A bunch of traditional nursery rhymes, this book is a must for all little ones. Illustrated beautifully with vibrant colours and printed in large font, the book is a delight with the colourful characters of Humpty Dumpty, Georgie porgie, little beyond-peep, Jack and Jill and others. Explore their charming topsy-turvy world, in simple and easy verse".
Twinkle, Twinkle little Star, Teddy Bear, Baa Baa Black Sheep, Rain Rain Go Away, dickery Dickery Dare.
Large Print Nursery Rhymes
Keywords: Nursery Rhymes; Comptines